ANALYSIS OF HOUSEHOLDS DIETARY DIVERSITY ON LEGUME CROPS INTERVENTION OF KANO STATE AGRICULTURAL AND RURAL DEVELOPMENT AUTHORITY/KANO STATE AGRO PASTORAL DEVELOPMENT PROJECT - Sani, U.; kurawa, F.; Ibrahim, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The household dietary diversity survey was carried out to assess the food security status among the beneficiaries of legume crops intervention of Kano Agricultural and Rural Development Authority (KNARDA)/ Kano Agro-pastoral development project. Eighteen local government areas were selected across the three KNARDA zones. One hundred and eight (108) groundnut, cowpea and soybeans farmers respectively were randomly selected, making a total of 324 beneficiaries. Data were collected using questionnaire and analyzed descriptive statistics. The findings revealed that the average age of the three value chain crops (groundnut, cowpea and soybeans) were 44, 43, and 45 years respectively. The average number of the household members among the value chain crops were 8, 7 and 7 members respectively. The mean monthly income were ₦106,925.93, ₦106,648.15 and ₦108,759.26 respectively. Average total farm size owned by the farmers of the value chain crops were 1.9ha, 1.9ha and 1.8ha respectively. Most of them were males 88.9%, 86.1% and 85.2% and married 95.4%, 95.4% and 95.4% respectively. The respondents possessed one form of education or the other with farming as one of the major means of livelihood 88.9%, 90.7% and 89.8% respectively. Majority (84.3%, 88.9% and 78.7%) of them belongs to cooperative or farmers group, respectively. The findings further revealed that majority of the beneficiaries of the three value chain crops ground nut (64.0%), cowpea (63.0%) and soybeans (59.0%) were above the acceptable food consumption score of 42.0 points. In addition, majority of cowpea (60.0%) and soybean (69.0%) beneficiaries had good dietary diversity with forty percent of groundnut beneficiaries having the same good dietary diversity. Furthermore, majority of the beneficiaries of the crops value chain groundnut (54.0%), cowpea (65.0%) and soybean (66.0%) had no hunger in their households. It was equally found that majority (66.0%, 84.0%, and 73.0%) for groundnut, cowpea and soybean respectively adopted low coping strategies against moderate and severe hunger. It was concluded that majority of the beneficiaries among the value chain crops were food secured. It is recommended that more support should be targeted toward the beneficiaries to uplift those at the severe hunger to food secured level.